Basic limonoid modulates chaperone-mediated proteostasis and dissolve Tau fibrils - Gorantla, Nalini Vijay; Das, Rashmi; Chidambaram, Hariharakrishnan; Dubey, Tushar; Mulani, Fayaj A.; Thulasiram, V. Hirekodathakallu; Chinnathambi, Subashchandrabose (Scientific Reports, 2020)
The Alzheimer's disease pathology is associated with accumulation of intracellular neurofibrillary tangles and extracellular senile plaques. The formation of initial nucleus triggers conformational changes in Tau and leads to its deposition. Hence, there is a need to eliminate these toxic proteins for proper functioning of neuronal cells. In this aspect, we screened the effect of basic limonoids such as gedunin, epoxyazadiradione, azadirone and azadiradione on inhibiting Tau aggregation as well as disintegration of induced Tau aggregates. It was observed that these basic limonoids effectively prevented aggregates formation by Tau and also exhibited the property of destabilizing matured Tau aggregates. The molecular docking analysis suggests that the basic limonoids interact with hexapeptide regions of aggregated Tau. Although these limonoids caused the conformational changes in Tau to beta-sheet structure, the cytological studies indicate that basic limonoids rescued cell death. The dual role of limonoids in Tau aggregation inhibition and disintegration of matured aggregates suggests them to be potent molecules in overcoming Tau pathology. Further, their origin from a medicinally important plant neem, which known to possess remarkable biological activities was also found to play protective role in HEK293T cells. Basic limonoids were non-toxic to HEK293T cells and also aided in activation of HSF1 by inducing its accumulation in nucleus. Western blotting and immunofluorescence studies showed that HSF1 in downstream increased the transcription of Hsp70 thus, aggravating cytosolic Hsp70 levels that can channel clearance of aberrant Tau. All these results mark basic limonoids as potential therapeutic natural products.